Hypoxic pulmonary hypertension in chronic lung diseases: novel vasoconstrictor pathways. Issue 3 (March 2016) - Rowan, Simon C; Keane, Michael P; Gaine, Seán; McLoughlin, Paul
Summary: Pulmonary hypertension is a well recognised complication of chronic hypoxic lung diseases, which are among the most common causes of death and disability worldwide. Development of pulmonary hypertension independently predicts reduced life expectancy. In chronic obstructive pulmonary disease, long-term oxygen therapy ameliorates pulmonary hypertension and greatly improves survival, although the correction of alveolar hypoxia and pulmonary hypertension is only partial. Advances in understanding of the regulation of vascular smooth muscle tone show that chronic vasoconstriction plays a more important part in the pathogenesis of hypoxic pulmonary hypertension than previously thought, and that structural vascular changes contribute less. Trials of existing vasodilators show that pulmonary hypertension can be ameliorated and systemic oxygen delivery improved in carefully selected patients, although systemic hypotensive effects limit the doses used. Vasoconstrictor pathways that are selective for the pulmonary circulation can be blocked to reduce hypoxic pulmonary hypertension without causing systemic hypotension, and thus provide potential targets for novel therapeutic strategies.